Traditional Features of Spanish Folktales - A. V. Bakanova (Ибероамериканские тетради)
Traditional folktales are an essential part of the Spanish folklore heritage. Folktales have echoes of the ancient mythological worldview and people’s experience accumulated over centuries. In Spanish, the term cuento is used in combination with the following adjectives: cuento folclórico, cuento popular, cuento tradicional. The traditional features of a folktale include a concise prosaic form, fantastical elements, a special chronotope, static characters, a fixed composition, language rich in traditional elements and mnemonics. Animal tales are considered the most ancient, then other types of folktales arose. Spanish folklorists distinguish such genres as cuentos novelescos, cuentos maravillosos, cuentos humanos varios, chistes y anécdotas, cuentos ejemplares y morales, cuentos religiosos, cuentos de nunca acabar, cuentos de fórmulas fijas. Spanish researchers’ interest in folktales grew in the 19th century, when a substantial body of folklore was accumulated thanks to the work of costumbrists and positivists. The philological study of Spanish folktales begins with the collections of A.M. Espinosa. Animal tales, as well as magical ones, are similar to the texts of the European tradition. The former often have a plot derived from antiquity and medieval bestiaries, while the latter share a unique compositional structure analyzed by V. Propp. The language of Spanish folklore is rich in formulas. The initial formulas open the world of the folktale, the intermediate ones serve to develop the plot, and the final ones emphasize the fictional features of the story. Household tales highlight national peculiarities the most as they depict traditional Spanish occupations and details of everyday life, explore moral issues and popular humor.